Sensory and hedonic impact of the replacement of synthetic antioxidant for pink pepper residue extract in chicken burger - Saldaña E. (2020)
This study aimed to evaluate the sensory and hedonic perceptions of chicken burger manufactured with pink pepper residue extract (PPE) added to the meat and to the chitosan film. Five samples were manufactured: CT: control, without antioxidant; DP and FP: addition of PPE to the meat batter and to the film, respectively; C1 and C2: commercial brands of chicken burgers. Consumers characterized the samples using the overall liking test and Check-all-that-apply questions. The samples showed a medium–high level of acceptance and no significant differences were found between them. DP was the farthest sample from the ideal and FP showed positive results, since its characteristics were like the commercial samples. The direct extract application may lead to a reduction in the liking of chicken burgers, demonstrating that the technology of active films is a viable alternative to the use of natural antioxidant extracts in meat products. © 2019, Association of Food Scientists & Technologists (India).